2018
DOI: 10.1186/s40644-018-0172-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pancreatic tumor development in KPC mice using multi-parametric MRI

Abstract: BackgroundPancreatic ductal adenocarcinoma (PDA) is a fatal disease with very poor prognosis. Development of sensitive and noninvasive methods to monitor tumor progression in PDA is a critical and unmet need. Magnetic resonance imaging (MRI) can noninvasively provide information regarding underlying pathophysiological processes such as necrosis, inflammatory changes and fibrotic tissue deposition.MethodsA genetically engineered KPC mouse model that recapitulates human PDA was used to characterize disease progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…17,22,23 Careful reading of the literature, however, reveals somewhat contradictory observations between different studies focusing on different contrasts; it has therefore been suggested that multiparametric explorations may be the best way to complement MRCP to target this type of tumor early. 17,24,25 While the aforementioned contrast sources seek correlations with morphological features, another relevant source of contrast may arise from metabolic markers. Although much has been done to elucidate the unique metabolic pathways underlying PDAC from a biological perspective, 26 few molecular imaging approaches have been derived from these and translated into a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,22,23 Careful reading of the literature, however, reveals somewhat contradictory observations between different studies focusing on different contrasts; it has therefore been suggested that multiparametric explorations may be the best way to complement MRCP to target this type of tumor early. 17,24,25 While the aforementioned contrast sources seek correlations with morphological features, another relevant source of contrast may arise from metabolic markers. Although much has been done to elucidate the unique metabolic pathways underlying PDAC from a biological perspective, 26 few molecular imaging approaches have been derived from these and translated into a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetization transfer (MT) has also been correlated with fibrosis, and has been shown in some cases as a good potential source of contrast 17,22,23 . Careful reading of the literature, however, reveals somewhat contradictory observations between different studies focusing on different contrasts; it has therefore been suggested that multiparametric explorations may be the best way to complement MRCP to target this type of tumor early 17,24,25 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, glucoCEST at 3 T is not yet practicable in body regions and physical movements and the effects of and made the originally small glucoCEST signal difficult to detect. Nasopharyngeal [ 102 ] and pancreatic cancers [ 106 , 107 , 108 , 109 , 110 ] were studied in animal models. CEST was used to detect tumor [ 108 , 109 , 110 ] and characterize the tumor tissue dynamically during therapy [ 102 , 106 , 107 ].…”
Section: Discussion and Future Prospectsmentioning
confidence: 99%
“…Whole tumor volumes were reconstructed from T1W tumor anatomy scans using the Amira software platform (Visualization Sciences Group, Burlington, MA, USA). Details of the MRI protocols employed are presented in Table 1 (see also [21,25]). We employed a water saturation shift referencing (WASSR) modification to CEST imaging as described by others for pre-clinical applications at high Tesla magnet strength [26,27,28].…”
Section: Methodsmentioning
confidence: 99%